323 A MULTIDISCIPLINARY QUALITY IMPROVEMENT PROJECT FOR MANAGING NON-COGNITIVE SYMPTOMS OF DEMENTIA IN ACUTE CARE. (25th October 2022) - Allen, Y; Foubert, M; Curtin, D; Hennessy, C; Twomey, N; Galvin, AM; Naughton, C
Abstract: Background: Over 80% of patients with dementia in acute care hospitals are prescribed an antipsychotic drug (INAD2) for management of Non-Cognitive Symptoms of Dementia (NCSD). Antipsychotics have a high side effect burden including increased mortality. Non-pharmacological interventions are first line management but many acute care wards are poorly equipped to deliver such interventions. The project aims to improve management of patients' NCSD and reduce pro re nata (PRN)/stat and intra-muscular (IM) antipsychotic prescribing in an acute care older adult ward. Methods: Using Plan-Do-Study-Act cycles (PDSA) a multicomponent intervention was iteratively designed and the implementation strategy is being tested. The components includes: an antipsychotic decision algorithm, Clinical Nurse Specialist (CNS) led patient review, patient behaviour charts, staff education and one-to-one coaching by CNS, patient 'Get-to-Know-Me' document and distraction resources. The evaluation involves a monthly point-prevalence audit of patient drug charts. Results: Over a seven-month period, baseline data indicated wide variability in patterns of antipsychotic prescribing. A median of 14 patients per month (min 7, max 18) were prescribed an antipsychotic drug, a median of five patients (min 3, max 12) were prescribed PRN antipsychotics and a median of two patients (min1, max3) received one or more IM injection for NCSD. There was often little information on the reason for administering PRN antipsychotic medication. There was some evidence of reduced PRN and IM medication for new patient admissions (0-4 doses), but individual patients with prolonged hospital stays had high levels of antipsychotic use. Conclusion: Reducing reliance on antipsychotic drugs requires multicomponent intervention and MDT collaboration. This intervention focussed primarily on coaching of healthcare professionals and improving the quality and consistency of prescribing. However, much more is required on environment design and access to cognitively stimulating activities to achieve a sustained improvement in patient outcomes, especially patients who experience a prolonged hospital stay.